PENGARUH GAYA KOMUNIKASI AKUN INSTAGRAM FOLKATIVE TERHADAP ONLINE ENGAGEMENT (STUDI KASUS MAHASISWA ILMU KOMUNIKASI UNIVERSITAS NEGERI JAKARTA ANGKATAN 2019) (KOMUNIKOLOGI : Jurnal Ilmiah Ilmu Komunikasi, 2021)
AbstractThe Folkative Instagram account is an online media platform that focuses on news, art, culture and local Indonesian products. Folkative is a collective company that focuses on young people, especially millennials. Folkative was created to inspire, inform and represent the voice of the creative culture of young people in Indonesia. Folkative does this by creating interactive online content and events worthy of being known by young people. From the results of the simple linear regression test, the coefficient of determination is 0.610 which means that there is a strong influence of the communication style of the Instagram folkative account on online involvement by 61%, which means that the Instagram folklive account communication style has an effect on online involvement of communication science students at the State University of Jakarta.Keywords : Communication Style, Folkative, Engagement AbstrakAkun Instagram Folkative merupakan salah satu platform media online yang berfokus pada berita, seni, budaya, dan produk lokal Indonesia. Folkative adalah perusahaan kolektif yang berfokus pada kaum muda, khususnya kaum millenial. Folkative diciptakan untuk menginspirasi, menginformasikan dan mewakili suara budaya kreatif anak muda di Indonesia. Folkative melakukannya dengan membuat konten online interaktif dan acara yang layak untuk diketahui anak muda. Dari hasil uji regresi linier sederhana didapatkan koefisien determinasi sebesar 0,610 yang berarti adanya pengaruh kuat dari gaya komunikasi akun Instagram folkative terhadap keterlibatan sevara daring sebesar 61% yang artinya gaya komunikasi akun Instagram folkative berpengaruh terhadap keterlibatan secara daring mahasiswa ilmu komunikasi Universitas Negeri Jakarta.Kata Kunci : Gaya Komunikasi, Fokative, Keterlibatan